The Date List of the Babylonian King Samsu-ditana - Feigin, S. I.
1. Babylonian King List В and the Number of Years of the Reign of Samsu-ditana — 2. The Known Date Formulas of Samsu-ditana — 3. The Date List of Samsu- ditana — 4. The Date Formula of the First Year — 5. The Custom of Naming the Second and Subsequent Years applied by the Predecessors of Samsu-ditana — 6. The Second and Subsequent Date Formulas of Samsu-ditana — 7. The Content of Date Formulas 2-5 — 8. Date Formulas 6-21 — 9. Date Formulas 22-26 (or 27). — 10. The Problems of the Reverse. — 11. The Unassigned Date Formulas.